A Panoramic Study of the Morphology of Mandibular Condyle in a Sample of Population from Basrah City - Aqeel-Al-Saedi,Ibrahim Lazim (Sociedad Chilena de Anatomía, 2020)
SUMMARY: The study aims to evaluate the morphological variation of mandibular condyle This analysis was composed of 450 digital orthopantomograms taken for routine investigation to assess the morphology of 900 condylar heads. Condylar morphology was classified into four types (oval, bird beak, diamond and crooked finger). Most common occurring shape were evaluated, symmetry of condylar shape and most common combinations of the condylar shapes present in population were assessed. Out of 900 mandibular condyle, type 1(oval) of condyle was the most commonly appearing shape (56 %), followed by type 3 (diamond), type 2(bird beak) and finally type 4 (crooked finger). Symmetry was seen in 74.2 % of the total sample with the oval-oval was the most commonly occurring. Routine use of orthopantomography can assist dentist in assessment of condylar morphology alterations. Oval shape was the most common in all age groups in males and females. More studies on Iraqi population evaluating mandibular condyle are needed to provide standardized values for mandibular anatomical parts.